Unpacking the forward guidance puzzle - SeHyoun Ahn (Norges Bank, 2024)
I prove that in any linearized general equilibrium model with existence and uniqueness of equilibrium, any present response to a future shock always becomes weaker the further away the shock is. There is no forward guidance puzzle in any sensible general equilibrium model if forward guidance is a one-time shock in the future. The difference from the literature arises from the underappreciated preceding peg of interest rate. The standard forward guidance exercise, of a drop in the interest rate in the future with the preceding peg of interest rate, is a series of explosive deviations disguised as a small, one-time shock in the future. I unpack the standard forward guidance exercise in different ways, and show that there is nothing puzzling about the forward guidance puzzle.
hdl:11250/3166745
Keywords: 330; Forward Guidance; DSGE-Modell; Schock; Zins; Theorie